Penggunaan foto pada latihan membaca dalam bahan ajar bahasa Indonesia bagi penutur asing: pendekatan semiotika sosial - Sinta Anggoro Utari; Harni Kartika-Ningsih (Jurnal Bahasa Indonesia bagi Penutur Asing, 2023)
In BIPA (Bahasa Indonesia untuk Penutur Asing or Indonesian for Foreign Speakers) teaching, photographs are one of the main sources used for providing visual support especially in reading sections. However, the effectiveness of using photos for teaching reading is not widely discussed. This article examines the use of photographs for learning reading. It seeks to reveal how photos can effectively scaffold learning activities and how photos and their accompanying texts build relationships. The study employs visual text analysis based on social semiotic frameworks - the representational metafunction and intersemiosis relationships. The findings reveals that conceptual photos dominate the type of photos, the composition of male and female participants was found to be equal and Concurrence-Clarification and Complementary-Augmentation was found as the majority of the intersemiosis relations. Several recommendations for BIPA teacher based on the conclusion are discussed at the end of this article.